Solar forcing of North Atlantic surface temperature and salinity over the past millennium - Moffa-Sánchez, P; Born, A; Hall, IR; Thornalley, DJR; Barker, S (2014)
There were several centennial-scale fluctuations in the climate and oceanography of the North Atlantic region over the past 1,000 years, including a period of relative cooling from about AD 1450 to 1850 known as the Little Ice Age. These variations may be linked to changes in solar irradiance, amplified through feedbacks including the Atlantic meridional overturning circulation. Changes in the return limb of the Atlantic meridional overturning circulation are reflected in water properties at the base of the mixed layer south of Iceland. Here we reconstruct thermocline temperature and salinity in this region from AD 818 to 1780 using paired δ18O and Mg/Ca ratio measurements of foraminifer shells from a subdecadally resolved marine sediment core. The reconstructed centennial-scale variations in hydrography correlate with variability in total solar irradiance. We find a similar correlation in a simulation of climate over the past 1,000 years. We infer that the hydrographic changes probably reflect variability in the strength of the subpolar gyre associated with changes in atmospheric circulation. Specifically, in the simulation, low solar irradiance promotes the development of frequent and persistent atmospheric blocking events, in which a quasi-stationary high-pressure system in the eastern North Atlantic modifies the flow of the westerly winds. We conclude that this process could have contributed to the consecutive cold winters documented in Europe during the Little Ice Age.